The sourcing arrangements of internal audit function (IAF) under COVID-19 pandemic: empirical evidence from emerging market - Waddah Kamal Hassan Omer (Cogent Business & Management, 2024)
AbstractThis study is purposed to analyse whether COVID-19 pandemic affects the sourcing arrangements IAF. This research uses the signaling theory framework and existing literature to establish hypotheses that are examined using probit regression. The analysis is conducted on a dataset comprising 141 company-year observations, all of which are publicly listed on the Muscat Stock Exchange during the 2019–2020 period. The result in the line with the study’s hypothesis, which refer to the significantly and negatively associated between the COVID-19 pandemic and the sourcing arrangements IAF. This study contributes to the theoretical and practical understanding of how the COVID-19 pandemic has influenced the sourcing arrangements of the Internal Audit Function (IAF) within an emerging Asian market, particularly in the context of Oman. It offers the initial empirical evidence of the relationship between the pandemic and IAF sourcing arrangements to the benefit of companies, auditors, shareholders, and regulatory bodies. The result offer contributions to the auditing and accounting literature as well as practice’s implications.